Jewish education and identity formation in The Netherlands after the Holocaust - Wingerden, Marjoke Rietveld‐van (2008)
The subject of this article is Dutch Jewish education since 1945, attended by some 20% of the Jewish children in the region of Amsterdam. I consider the motives of the advocates of Jewish day schools, for whom the Holocaust was an important argument from a psychological, educational, social and cultural perspective in rejecting multi‐religious education. For them the children damaged by war, and their offspring, needed a safe and familiar environment in which they would meet comprehension. Moreover, the Holocaust had become part of Jewish identity and had stimulated the study of roots and traditions for which Jewish schools would provide the foundation. However, these schools were confronted with social and political pressure to realise multi‐religious education as a necessary preparation for living together in a pluralist society. Jewish leaders disagreed with this point of view citing the aims of Jewish schools and their contribution to the civic education of Jewish pupils.
Keywords: Dutch Jews; Holocaust; Identity Formation; multicultural society; multi‐religious education